2019
DOI: 10.3390/jcm8040450
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sarcopenia with and Efficacy of Anti-PD-1/PD-L1 Therapy in Non-Small-Cell Lung Cancer

Abstract: Secondary sarcopenia is defined as a decrease in muscle mass due to disease or malnutrition. Several studies have reported that secondary sarcopenia is an indicator of postoperative recurrence. We hypothesized that there is a correlation between the effect of immune checkpoint inhibitors (ICIs) and sarcopenia. We retrospectively analyzed 38 patients with advanced non-small cell lung cancer (NSCLC) who were treated with ICIs between February 2016 and April 2018. Patients were divided into two groups according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 36 publications
3
87
4
Order By: Relevance
“…Similarly, Nishioka and colleagues evaluated the change in muscle mass over time in 38 NSCLC patients receiving PD-1 Inhibitors 11 . Even if not significant, they found a higher change rate (decrease in muscle mass) among patients with poorer PS (p = 0.056) 11 .…”
Section: Overallmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Nishioka and colleagues evaluated the change in muscle mass over time in 38 NSCLC patients receiving PD-1 Inhibitors 11 . Even if not significant, they found a higher change rate (decrease in muscle mass) among patients with poorer PS (p = 0.056) 11 .…”
Section: Overallmentioning
confidence: 82%
“…In a preliminary report, we found that sarcopenic non-small cell lung cancer (NSCLC) patients receiving nivolumab had shorter progression free survival (PFS) and overall survival (OS) 9 . Moreover, other two retrospective studies found a significant association between sarcopenia, shorter PFS and worse objective response rate (ORR) 10,11 .…”
mentioning
confidence: 99%
“…In addition, a lower BMI is associated with increased mortality risk [21][22][23][24]. Our previous clinical study demonstrated that NSCLC patients with sarcopenia exhibit a significantly shorter median PFS following ICI treatment compared to that of non-sarcopenia patients [25]. Given these observations, a poor ECOG-PS and a low BMI at the time of ICI treatment intervention may be useful for predicting non-responders to initial ICI treatment, as well as ICI rechallenge treatment among patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Recently, the psoas muscle index (PMI), which indicates the degree of skeletal muscle atrophy, has attracted attention for the purpose of assessing the severity of cancer-induced sarcopenia. 13,16 Thus, various indicators reflecting cancer severity affecting the general condition or sarcopenia have been identified, whereas their significance has continued to be elucidated.…”
Section: Introductionmentioning
confidence: 99%